Enhancing the Stability of Aerobic Granular Sludge Process Treating Municipal Wastewater by Adjusting Organic Loading Rate and Dissolved Oxygen Concentration - Juan Peng; Lei Zhao; Qiaoru Wang; Wei Song; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Fang Yuan (Separations, 2022)
Aerobic granular sludge (AGS) application in treating municipal wastewater has been greatly restricted due to its low stability. It has been found that operation parameters have a great impact on stability. The organic loading rate (OLR) and dissolved oxygen (DO) concentration are two very important parameters that impact stability. In this study, the organic loading rate (OLR) and aeration rate were studied to verify their influence on AGS system stability, which is indicated by determining pollutant removal performance, including chemical oxygen demand (COD), ammonia nitrogen, and total nitrogen (TN). The physical and chemical property changes of AGS and the effects of pollutant removal during the formation of AGS were systematically investigated. The AGS was formed after about 25 days and remained stable for about 45–50 days. The AGS was light-yellow globular sludge with an average particle size of 1.25 mm and a sludge volume index (SVI) of 33.9 mL/g. The optimal condition was obtained at an OLR of 4.2 kg COD/m3·d, aeration rate of 4 L/min, and a hydraulic retention time (HRT) of 4 h. The corresponding removal efficiencies of COD, ammonia nitrogen, and TN were 94.1%, 98.4% and 74.1%, respectively. The study shows that the AGS system has great potential for pollutant removal from wastewater.